Inadequate Funding and the Development of University Education in Nigeria: Challenges and Way Forward - Bello, Sirajo; Umar, Umar Abdulkadir; Usman, Lurwanu (Mahesa Research Center, 2025)
The lack of political leaders' commitment resulted in inadequate funding for tertiary institutions in Nigeria. This has been a significant issue for the advancement of university education, presenting numerous challenges that negatively impact the development of Nigeria’s public universities. This paper examines the challenges posed by inadequate funding for university education development in Nigeria and proposes possible solutions. The study employed a qualitative approach and used Nigerian public universities as the case study. The study was also guided by the Resource Dependency Theory, as proposed by Pfeffer and Salanick (1978). The findings of the study revealed that there are poor infrastructural facilities, poor staff development, low international ranking, series of strike actions, brain-drain of academics, poor research development and non-attraction of international students Therefore the study recommended among others that political leaders in Nigeria at both federal and state levels should increase budgetary allocation to education sector to enable effective development of university education. There is also a need for private and non-governmental organisations to complement the government's efforts to improve university education by providing infrastructure, such as electricity, water supply, road networks, student hostels, staff housing, and the like, in universities. University administrators should enhance the sources of internally generated revenue and ensure that the funds realised from internal sources are utilised judiciously to promote the positive development of university education in Nigeria.